Some people need killing a memoir of murder in my country - Evangelista, Patricia (Random House, 2023)
"'My job is to go to places where people die. I pack my bags, talk to the survivors, write my stories, then go home to wait for the next catastrophe. I don't wait very long.' Journalist Patricia Evangelista came of age in the aftermath of a street revolution that forged a new future for the Philippines. Three decades later, in the face of mounting inequality, the nation discovered the fragility of its democratic institutions under the regime of strongman Rodrigo Duterte. Some People Need Killing is Evangelista's meticulously reported and deeply human chronicle of the Philippines' drug war and Duterte's assault on the country's struggling democracy. For six years, Evangelista had the distinctive beat of chronicling the killings carried out by police and vigilantes in the name of Duterte's war on drugs - a war that has led to the slaughter of thousands - immersing herself in the world of killers and survivors and capturing the atmosphere of fear created when an elected president decides that some lives are worth less than others"--